Effect of osmotic stress on antioxidant enzyme activities in transgenic wheat calli bearing MsALR gene - Csiszár, Jolán (Acta Biologica Szegediensis, 2005)
The antioxidant enzyme activities were studied in transgenic wheat calli bearing alfalfa MsALR gene. The effect of 14% PEG treatment was studied measuring the activities of some hydrogen peroxide related enzymes (SOD, CAT, POD) and the glutathione related GR, GST and GS-PX enzymes. Induction of the antioxidant enzymes is usually a complex process, one enzyme alone supposedly can not ensure enough protection under stress conditions. Our results showed that the changes of antioxidant enzyme activities are characteristic for the cultures. Some calli had higher activities of antioxidant enzymes than untransformed controls even in control circumstances. There are transgenic wheat calli with elevated SOD, CAT and/or POD activities, while in some other calli the activities of the glutathione related enzymes (GR, GS-PX) were increased comparing to the control.